2014
DOI: 10.1007/s11062-014-9410-0
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sleep Characteristics and Mild Cognitive Impairment in Elderly People

Abstract: We compared the sleep quality indices between patients with mild cognitive impairment (MCI) and normal elderly subjects and analyzed the effects of sleep characteristics on cognitive functions. Cases of MCI patients (320 persons, MCI group) and 630 normal elderly with matched age, gender, and level of education (control group) were enrolled in this study. The Pittsburgh Sleep Quality Index (PSQI) was used to assess the sleep characteristics. The Mini-Mental State Examination (MMSE) and Montreal Cognitive Asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…As expected, poor sleep quality was linked with deficits in cognition, which previous studies have likewise found . These deficits are reflected mainly in low reading and language comprehension and an impaired attention span …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As expected, poor sleep quality was linked with deficits in cognition, which previous studies have likewise found . These deficits are reflected mainly in low reading and language comprehension and an impaired attention span …”
Section: Discussionsupporting
confidence: 81%
“…22 These deficits are reflected mainly in low reading and language comprehension and an impaired attention span. 23 In this sample, the most common factors in the sleep disturbance component were 'Wake up in the middle of the night or early morning' and 'Have to get up to use the bathroom'. These results are not surprising: older adults may develop an increased risk of insomnia with advancing age, and the presence of nocturia can affect night-time sleep.…”
Section: Discussionmentioning
confidence: 85%
“…4 This effect of sleep on cognition was evident even when comparing individuals with mild cognitive impairment (MCI) with sleep disorders to MCI patients without sleep disorders, whereby the latter had significantly higher scores in domains such as attention, visuo-spatial/executive function compared to the former. 27 One possible reason for the insignificant finding in this study might be due to the limited number of cognitive domains that were examined in relation to sleep problems. Past studies, such as that by Blackwell et al, 28 have found sleep disruptions at different sleep stages to be associated with deficits in various cognitive domains, particularly executive functioning.…”
Section: Discussionmentioning
confidence: 75%
“…found 24% of good sleepers to have cognitive deficits compared to 52% of poor sleepers on the Mini‐Mental State Examination . This effect of sleep on cognition was evident even when comparing individuals with mild cognitive impairment (MCI) with sleep disorders to MCI patients without sleep disorders, whereby the latter had significantly higher scores in domains such as attention, visuo‐spatial/executive function compared to the former …”
Section: Discussionmentioning
confidence: 96%
“…Sample size calculations were performed using PASS 15.0 24 for Testing Two Proportions using the Z-Test. Based on a previous study which reported 34.3% and 27% of cases with sleep disturbance in the MCI and normal cognition groups, 25 the power and type 1 error probability were set at 0.80 and 0.05, respectively. Under these assumptions, a minimum of 1,246 participants were needed to evaluate the prevalence of sleep disturbance among mild cognitively impaired and noncognitively impaired older adults.…”
Section: Sample Size Calculationmentioning
confidence: 99%